Typology of digital leadership roles tasked with integrating new technologies into teaching: Insights from metaphor analysis. Issue 1 (1st January 2022) - Avidov-Ungar, Orit; Shamir-Inbal, Tamar; Blau, Ina
Abstract: This research explored how digital leaders, being teachers responsible for integrating technologies into teaching, envisaged their roles. Bottom-up content analysis of metaphors from 55 digital leaders revealed a typology describing them as change agents across three 'extent' and two 'depth' dimensions. Most leaders described the extent of change associated with their role consistently with the Islands of Innovation and Comprehensive Innovation frameworks, rather than the broader School Communities of Innovation approach. Most metaphors reflected superficial change rather than fundamental change. Although the digital leader role was created to spur innovative change, this is not how most educational practitioners envisage it.